Evaluasi Kinerja Keuangan Melalui Pendekatan Value For Money - Abdul Hamid; Ilyas Lamuda (Gorontalo Accounting Journal, 2019)
The purpose of this study is to test and analyze the effect of the element of value for money which consists of economics, efficiency, the effectiveness of the financial performance of the Marine and Fisheries Office of Sidoarjo Regency. The analytical tool used in this study is using multiple linear regression.The results of the study show that element value for money consists of economics, efficiency, influential effectiveness together with the financial performance of the Department of Marine and Fisheries of Sidoarjo Regency. The economic value of value for money influences the financial performance of the Sidoarjo Regency Marine and Fisheries Office, the efficiency value of value for money influences the financial performance of the Sidoarjo Regency Marine and Fisheries Service. Test the coefficient of determination of R² obtained is 0.701 or 70.1% and the remaining 29.1% is explained by other variables outside of this research model.